Rethinking productive development sound policies and institutions for economic transformation - Crespi, Gustavo; Fernandez-Arias, Eduardo; Inter-American Development Bank (New York Palgrave Macmillan, 2014)
"Rethinking Industrial Policy systematically analyzes policies in key areas such as innovation, new firms, firm networks, financing, human capital, and internationalization. The authors provide an in-depth look at specific policies and institutions that illustrate the do's and don'ts emerging from regional and international experience on the basis of the analytic tests, and they review new approaches to gauging the opportunities countries have for beneficial productive transformation into new and better products. The book discusses how these analyses are useful to inform policy to stimulate and guide productive transformation"-- Provided by publisher.
"Productive transformation requires seizing the opportunities available and opening new ones in a competitive world. This book rethinks productive development by examining the market failures impeding transformation and the government failures that may make the policy remedies worse than the market illness. To address market failures, the authors propose a simple conceptual framework based on the scope and nature of the policy approach. They then systematically analyze country policies through this lens in key areas such as innovation, new firms, financing, human capital, and internationalization to show the power of this way of thinking. Still, the book warns that policymakers cannot be sure what the right policy interventions are and must set up a process to discover them that calls for public-private collaboration. Recognizing that the risk of capture needs to be checked and that even the best policies will fail without the technical, organizational, and political capacity to implement them, the book concludes with ideas on how to design institutions fostering the right incentives and how to grow public sector capabilities over time"-- Provided by publisher.
Machine generated contents note: -- 1.Industrial Policy in Latin America: Past and Present2.An Analytical Framework to Rethink Industrial Policy3.Innovation and Diffusion4.Firm Creation and Development5.Productive Linkages among Firms6.Financing for Development7.Productive Human Capital8.Internationalization for Productive Development9.Seizing the Opportunities for Productive Transformation10.Productive Development Policy as a Learning Process11.Growing and Deploying Public-Sector Institutional Capacities12.Building Sound Institutions for Public-Private Collaboration.
Includes bibliographical references and index.
Keywords: New business enterprises; Industrial policy